Post-Traumatic Stress Disorder among Defence and Security Forces in Northern Benin (2023) - AZA-GNANDJI, Guy-Gérard (My University, 2024)
Introduction: Post-traumatic stress disorder (PTSD) is defined as “actual exposure to death or the threat of death, serious injury or sexual violence”, either directly or indirectly, resulting in a symptomatic procession of repeti tion, avoidance, neurovegetative hyperactivity and individualized symptoms, with or without negative cognitive and mood changes. It therefore goes without saying that the defence and security forces constitute a high-risk population in need of attention. Objective: To study post-traumatic stress disorder in defence and security forces in the city of Parakou in 2023. Methods: Descriptive cross-sectional study conducted from December 2022 to July 2023. The study population consisted of active military, republican police and firefighters in the city of Parakou in 2023. Non-proportional stratified sampling was used, given the inaccessibility of the source population size for national security reasons. Post-traumatic stress disorder was assessed using the “post-traumatic stress disorder checklist-5 (PCLS-5) scale. Results: A total of 305 subjects participated in the survey. Males dominated 90.2%. The most represented corps was the Republican Police (41.6%), most of whom were non-commissioned officers (46.6%). The majority count between 11 and 20 years of service (48.9%), with 2 to 5 missions completed (67.5%). The calculated prevalence of post- traumatic stress disorder was 11.8%, based on the post-traumatic stress dis order checklist-5 (PCL-5). Of the 36 respondents with post-traumatic stress disorder, 20 (55.6%) had experienced an armed attack, 25 (69.4%) had wit nessed a violent death, 18 (50.0%) had witnessed the agony of a colleague, 15 (41.7%) had been exposed to a fire or explosion, while 26 (72.2%) had been traumatized by physical and/or verbal aggression. 5 (13.9%) had consulted a specialist psychiatrist, while 6 (16.7%) were on medication and 26 (72.2%) used sport as a means of maintaining physical and mental health. Respective ly 22 (61.1%) and 21 (58.3%) had definite symptoms of anxiety and depression. Multivariate analysis revealed a significant association between post-traumatic stress disorder and the following variables: total number of children ≤ 2 (p = 0.015), comorbidities such as arterial hypertension (p = 0.007), history of he patitis (p = 0.017), work accidents (p = 0.016), alcohol dependence (p = 0.004), domestic violence (p = 0.004), psychological violence (p = 0.017) and anxiety disorders (p < 0.001). Conclusion: Defence and security personnel can also be prey to post-traumatic stress disorder (PTSD), which needs to be systematically taken into account when they are subjected to trauma in the course of their duties. Mental health should be an integral part of the periodic medical check-up objectives for defence and security forces throughout the country.
Keywords: Post-Traumatic Stress Disorder; Forces; Defence; Security; Benin; 2023